2019
DOI: 10.1186/s13045-019-0710-0
|View full text |Cite
|
Sign up to set email alerts
|

Early myeloid-derived suppressor cells (HLA-DR−/lowCD33+CD16−) expanded by granulocyte colony-stimulating factor prevent acute graft-versus-host disease (GVHD) in humanized mouse and might contribute to lower GVHD in patients post allo-HSCT

Abstract: IntroductionMyeloid-derived suppressor cells (MDSCs) are proposed to control graft-versus-host disease (GVHD) in allogeneic hematopoietic stem cell transplantation (allo-HSCT). However, the definition of human MDSCs has not yet reached consensus, and the mechanism of MDSCs to control GVHD remains unclear.MethodsImmature myeloid cells (HLA-DR−/lowCD33+CD16−) were tested before and after granulocyte colony-stimulating factor (G-CSF) administration in healthy donor and isolated for suppression assays and co-cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 56 publications
1
34
0
Order By: Relevance
“…Fan demonstrated that a higher frequency of MDSCs (Lin low/neg HLA-DR − CD33 + CD11b + ) in the G-CSF primed BM than in the G-CSF peripheral blood stem cells harvest (G-PBSC) grafts lead to a better GVHD and relapse-free survival (GRFS) and less GVHD [65]. Wang identified a new subset of eMDSCs (HLA-DR−/lowCD33 + CD16- cells) in a humanized mice model that may control acute GVHD in mice HSCT, and these cells were also identified as an independent factor that reduced the occurrence of grade II-IV aGvHD in allo-HSCT patients [66]. Schneidawind reported that administration of G-CSF- donor lymphocyte infusion (DLI) results in graft-versus-leukemia effects without exacerbating GVHD because of the M-MDSCs in the DLI component [67].…”
Section: Are Mdscs Always Associated With Poor Outcomes In Hematologimentioning
confidence: 99%
“…Fan demonstrated that a higher frequency of MDSCs (Lin low/neg HLA-DR − CD33 + CD11b + ) in the G-CSF primed BM than in the G-CSF peripheral blood stem cells harvest (G-PBSC) grafts lead to a better GVHD and relapse-free survival (GRFS) and less GVHD [65]. Wang identified a new subset of eMDSCs (HLA-DR−/lowCD33 + CD16- cells) in a humanized mice model that may control acute GVHD in mice HSCT, and these cells were also identified as an independent factor that reduced the occurrence of grade II-IV aGvHD in allo-HSCT patients [66]. Schneidawind reported that administration of G-CSF- donor lymphocyte infusion (DLI) results in graft-versus-leukemia effects without exacerbating GVHD because of the M-MDSCs in the DLI component [67].…”
Section: Are Mdscs Always Associated With Poor Outcomes In Hematologimentioning
confidence: 99%
“…In recent studies, MDSCs have potential for the treatment of GVHD [16,17,34]. However, our data show that MDSCs alone had low clinical e cacy.…”
Section: Discussionmentioning
confidence: 64%
“…In recent studies, MDSCs have potential for the treatment of GVHD [ 16 , 17 , 34 ]. However, our data show that MDSCs alone had low clinical efficacy.…”
Section: Discussionmentioning
confidence: 99%